A brainstem syndrome associatedxb with Mycoplasma pneumoniae infection—A report of two cases. Issue 597 (July 1975) - Jachuck, S. J.; Gardner-Thorpe, C.; Clark, F.; Foster, J. B.
Abstract : Two patients with a serologically-proved infection with Mycoplasma pneumoniae (MP) developed cranial nerve pareses which cleared spontaneously within 1 month of the onset. The sixth and seventh cranial nerves were the most severely affected. It is suggested that the signs were due to a mild brainstem encephalitis associated with the MP infection. The benign course of the syndrome is emphasized. The neurological complications of MP infection may be commoner than has been generally supposed.